She Works, Therefore She Worries: The Hidden Costs of Balance for Women in Indonesian Banking - Suhartini, Eka; Kankaew, Kannapat; Syariati, Alim (Jurnal Manajemen Bisnis, 2025)
Research aims: This study investigates how work–family conflict, job stress, and social support interact to shape women’s work–life balance in the Indonesian banking sector. It contributes to the work–life literature by recontextualizing classical stress and role theories within a gendered, post-pandemic professional setting in a developing economy.Design/Methodology/Approach: This study distributes a structured questionnaire 197 female professionals across multiple banking institutions, and the data is analyzed using PLS-SEM.Research findings: The findings reveal that while work–family conflict does not directly reduce work-life balance, it significantly elevates job stress, which in turn diminishes perceived balance. Social support mitigates the negative impact of stress but does not attenuate the effects of conflict itself.Theoretical Contribution/Originality: This study extends the theory of conservation of resources (COR), role theory, as well as the job demands–resources (JD-R) model by proposing a moderated mediation framework in which job stress mediates the relationship between work–family conflict and work–life balance, while social support serves as a conditional buffer.Practitioners/Policy Implications: These insights advance theoretical understanding and provide actionable insights for designing gender-responsive human resource policies and systems in high-pressure service sectors.Research Limitations/Implications: Future studies should integrate variables such as digital surveillance, algorithmic task allocation, and technostress to capture the impact of new and emerging technologies on work–life dynamics, particularly for women.